2014
DOI: 10.2131/jts.39.331
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acid-rich diet improves skeletal muscle wasting caused by cigarette smoke in rats

Abstract: -Cigarette smoke induces skeletal muscle wasting by a mechanism not yet fully elucidated. Branched-chain amino acids (BCAA) in the skeletal muscles are useful energy sources during exercise or systemic stresses. We investigated the relationship between skeletal muscle wasting caused by cigarette smoke and changes in BCAA levels in the plasma and skeletal muscles of rats. Furthermore, the effects of BCAA-rich diet on muscle wasting caused by cigarette smoke were also investigated. Wistar Kyoto (WKY) rats that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…4C-G). In a recent study, Tomoda and colleagues analyzed the levels of BCAA-related metabolites and identified a significant decreased in BCAA levels in both plasma and skeletal muscles of rats exposed to CS 23 . We further detected a decrease of 1-carboxyethylleucine in lens FC of mice exposed to CS.…”
Section: Resultsmentioning
confidence: 99%
“…4C-G). In a recent study, Tomoda and colleagues analyzed the levels of BCAA-related metabolites and identified a significant decreased in BCAA levels in both plasma and skeletal muscles of rats exposed to CS 23 . We further detected a decrease of 1-carboxyethylleucine in lens FC of mice exposed to CS.…”
Section: Resultsmentioning
confidence: 99%